2014
DOI: 10.1017/jfm.2014.589
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the roughness-induced transition: global stability analyses and direct numerical simulations

Abstract: . Investigation of the roughness-induced transition: global stability analyses and direct numerical simulations. Journal of Fluid Mechanics, Cambridge University Press (CUP), 2014, 760, pp.175-211. 10.1017/jfm.2014.589. hal-01086744 Science Arts & Métiers (SAM)is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. The linear global instability and resulting transition to turbulence induced by an isolated cylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
168
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(199 citation statements)
references
References 49 publications
(105 reference statements)
31
168
0
Order By: Relevance
“…The symmetrical distribution of the perturbation is consistent with the varicose-type mode in the wake of roughness element obtained by stability analysis ( On Reynolds number dependence of micro-ramp-induced transition 617 periodic shedding of hairpin vortices. As reported by Loiseau et al (2014), although the varicose mode appears initially at the wake centre, it propagates spanwise and occupies the whole domain width. However, in the present POD analysis, modes 1 and 2 remain confined within a limited spanwise range (z/h = [−0.5, 0.5]).…”
Section: Pod Analysissupporting
confidence: 59%
See 3 more Smart Citations
“…The symmetrical distribution of the perturbation is consistent with the varicose-type mode in the wake of roughness element obtained by stability analysis ( On Reynolds number dependence of micro-ramp-induced transition 617 periodic shedding of hairpin vortices. As reported by Loiseau et al (2014), although the varicose mode appears initially at the wake centre, it propagates spanwise and occupies the whole domain width. However, in the present POD analysis, modes 1 and 2 remain confined within a limited spanwise range (z/h = [−0.5, 0.5]).…”
Section: Pod Analysissupporting
confidence: 59%
“…Nevertheless, increasing both parameters leads to a fast growth of the perturbations, causing early transition. In the recent DNS study performed by Loiseau et al (2014), velocity streaks were also observed in the wake of discrete cylinders. Increasing Re h from a subcritical to supercritical value results in a longer streamwise persistence of a low-speed region around the symmetry plane.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…By increasing Re k in a two-dimensional boundary layer beyond a certain limit, Re k,t , the transition location has been noticed to move upstream to the trailing edge of the roughness (von Doenho↵ & Braslow 1961). Due to its importance for the development of laminar wings, the determination of Re k,t has been the subject of several global stability analyses (Loiseau et al 2014;Citro et al 2015;Kurz & Kloker 2016). For roughness elements in a Blasius boundary layer, the above mentioned flow-tripping was found to correspond to the onset of a global flow instability.…”
Section: Introductionmentioning
confidence: 99%